A Prospective Randomized Trial of N-butyl-cyanoacrylate + Metacryloxysulfolane Adhesive versus Suture Alone for Grafting in Rhinoplasty: 9 year Follow-up. (May 2021) - Martino, Carmine; Salzano, Francesco; Martino, Diletta; Ralli, Massimo; De Vincentiis, Marco; Maranzano, Massimo; Greco, Antonio; Salzano, Giovanni; Di Stadio, Arianna
Objective: Use of cyanoacrylate glue in facial plastic surgery is still controversial due to the absence of long-term follow up showing the results. Aim of our study is comparing the long-term outcomes of N-butyl-cyanoacrylate + Metacryloxysulfolane versus traditional sutures in rhinoplasty. Methods: Prospective comparative study. One hundred forty-two patients affected by ptotic nasal tip were included and randomized in two groups. In group A, the surgeon fixed the graft by using the glue and suture and in group B by using the traditional suture only. The following data were collected and compared by statistical analysis: nasolabial angle before and after surgery, dimensions of the graft, duration time (in minutes) for graft application during the surgery, number of sutures applied to fix the graft, presence of post-surgery negative outcomes. Results: All patients statistically improved their nasolabial angle after surgery (ANOVA: P < .0001) without statistically significant differences between the two groups both at short and long follow-up (χ: P = 1 and P = .9 respectively). A statistically significant difference in graft fixation time ( P < .00001) and number of sutures (t: P < .00001) used was observed between the two groups. No statistically significant difference was observed in prevalence of infection after surgery. Conclusion: N-butyl-cyanoacrylate + Metacryloxysulfolane could be a valid tool to reduce the necessary number of sutures and to reduce the time required for graft fixation graft fixation with consistent results in long-term follow-up.